2012
DOI: 10.1186/1297-9716-43-36
|View full text |Cite
|
Sign up to set email alerts
|

Inability of NS1 protein from an H5N1 influenza virus to activate PI3K/Akt signaling pathway correlates to the enhanced virus replication upon PI3K inhibition

Abstract: BackgroundPhosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway, activated during influenza A virus infection, can promote viral replication via multiple mechanisms. Direct binding of NS1 protein to p85β subunit of PI3K is required for activation of PI3K/Akt signaling. Binding and subsequent activation of PI3K is believed to be a conserved character of influenza A virus NS1 protein. Sequence variation of NS1 proteins in different influenza A viruses led us to investigate possible deviation from the conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Therefore, we speculate that, through a currently unknown mechanism, the interaction of NS1-ESEV (but not NS1-ESKV) with Dlg-1 stimulates the PI3K/Akt pathway, resulting in efficient virus replication. While this study was under way, Li et al (64) described an H5N1 influenza virus that no longer activated the PI3K/Akt pathway. The NS1 protein of this virus possesses the NS1-ESKV motif, consistent with our finding that NS1-ESKV affects PI3K/Akt activation.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we speculate that, through a currently unknown mechanism, the interaction of NS1-ESEV (but not NS1-ESKV) with Dlg-1 stimulates the PI3K/Akt pathway, resulting in efficient virus replication. While this study was under way, Li et al (64) described an H5N1 influenza virus that no longer activated the PI3K/Akt pathway. The NS1 protein of this virus possesses the NS1-ESKV motif, consistent with our finding that NS1-ESKV affects PI3K/Akt activation.…”
Section: Discussionmentioning
confidence: 94%
“…A PI3K inhibitor decreased expression of CD16 on microglial cells (central nervous system-resident macrophages), suggesting a link between PI3K signalling and Fc receptor expression [69]. Although seasonal H1N1 and H3N2 IAV activate the PI3K signalling pathway in mouse AMs, an H5N1 IAV fails to do the same in infected epithelial cells [70,71]. While the status of PI3K signalling in H5-infected macrophages has not been investigated, perhaps a failure to activate the PI3K pathway in macrophages is one explanation for the observed decrease in CD16/32 expression that leads to the decreased phagocytic capacity of H5-infected macrophages.…”
Section: Iav Replication and Macrophage Phagocytosismentioning
confidence: 99%
“…The products of the NS segment have indeed been implicated in host adaptation and pathogenicity. For instance, Li et al concluded that the NS1 gene contributed to the virulence of H5N1 avian influenza viruses ( 16 ), while adaptive mutations in both the NS1 protein and NEP were found when A/Hong Kong/1968 (H3N2) was adapted to increased virulence in mice ( 17 ).…”
Section: Introductionmentioning
confidence: 99%